Modeling temperature and residual stress fields in selective laser melting - Li, Yingli (2020)
The paper investigates the temperature and residual stress fields in the selective laser melting (SLM) process. A three-dimensional thermo-mechanical coupling model is developed to simulate a multi-track multi-layer SLM process using the finite element method. The model considers the temperature-dependent material properties which consist of thermal conductivity, density, enthalpy, yield stress, thermal expansion coefficient and Young's modulus. The simulated process includes the heating, melting, vaporization, solidification, shrinkage and cooling phenomena in the powder bed. The SLM scanning laser beam can be described as a moving volumetric heat source that is able to penetrate through the powder layers. The modeling results show that the residual stress component of the built part in the direction of the layer height increases with the number of the printed layers. It is found that at a given point, the residual stress component in the scanning direction is generally larger than the other two components, and the maximum von Mises stress occurs in the middle plane of the printed part. The temperature evolution and residual stress distribution predicted by the model can serve to provide guidance for SLM process parameter optimization.